Nonlinear S-Parameter Behavioral Model of a Photonic Radar Transceiver Chipset for Automotive Applications - Kruse, Stephan; Schwabe, Tobias; Kneuper, Pascal; Meinecke, Marc-Michael; Kurz, Heiko G.; Scheytt, J. Christoph
This paper presents a method to model monolithically integrated photonic radar transceiver (TRX) with optical local oscillator (LO) distribution in silicon germanium (SiGe) electronic photonic integrated circuits (EPICs). The model proposed approximates the behavior of the nonlinear scattering (S)-parameters and noise figure of each building block of the TRX chipset by Laplace polynomials and hyperbolic tangent functions. The modular approach of the model allows to optimize hardware components with respect to the entire TRX system, and fault identification with reduced computational effort. The proposed method is validated using the first monolithically integrated photonic radar transceiver chipset and shows excellent agreement with the post layout simulation results and, including the photodiode (PD) bandwidth (BW) degradation, also with the measurements.

On the structure of regularization paths for piecewise differentiable regularization terms - Gebken, Bennet; Bieker, Katharina; Peitz, Sebastian (Journal of Global Optimization)
Regularization is used in many different areas of optimization when solutions are sought which not only minimize a given function, but also possess a certain degree of regularity. Popular applications are image denoising, sparse regression and machine learning. Since the choice of the regularization parameter is crucial but often difficult, path-following methods are used to approximate the entire regularization path, i.e., the set of all possible solutions for all regularization parameters. Due to their nature, the development of these methods requires structural results about the regularization path. The goal of this article is to derive these results for the case of a smooth objective function which is penalized by a piecewise differentiable regularization term. We do this by treating regularization as a multiobjective optimization problem. Our results suggest that even in this general case, the regularization path is piecewise smooth. Moreover, our theory allows for a classification of the nonsmooth features that occur in between smooth parts. This is demonstrated in two applications, namely support-vector machines and exact penalty methods.

Numerical study of light backscattering from layers of absorbing irregular particles larger than the wavelength - Alhaddad, Samer; Förstner, Jens; Grynko, Yevgen (Journal of Quantitative Spectroscopy and Radiative Transfer)
Keywords: tet_topic_scattering

LoRa Transceiver for Load Monitoring and Control System in Microgrids - Mwammenywa, Ibrahim; Petrov, Dmitry; Holle, Philipp; Hilleringmann, Ulrich (2022 International Conference on Engineering and Emerging Technologies (ICEET))

Student Teachers ’ Knowledge of Congruence before a University Course on Geometry - Hoffmann, Max; Biehler, Rolf (Proceedings of the Fourth Conference of the International Network for Didactic Research in University Mathematics (INDRUM 2022, 19-22 October 2022))
Keywords: Teaching and learning of specific topics in university mathematics; Transition to; across and from university mathematics; Student Teachers; Geometry; Congruence; Double Discontinuity.

Innovations in university teaching based on mathematic education research - Florensa, Ignasio; Hoffmann, Max; Romo Vázquez, Avenilde; Zandieh, Michelle; Martínez-Planell, Rafael (Proceedings of the Fourth Conference of the International Network for Didactic Research in University Mathematics (INDRUM 2022, 19-22 October 2022))

Beep-and-Sleep: Message and Energy Efficient Set Cover - Götte, Thorsten; Kolb, Christina; Scheideler, Christian; Werthmann, Julian (Theor. Comput. Sci.)

Supporting Construction and Architectural Visualization through BIM and AR/VR: A Systematic Literature Review - Yigitbas, Enes; Nowosad, Alexander; Engels, Gregor (Proceedings of the 19th IFIP TC13 International Conference on Human-Computer Interaction (INTERACT 2023))

Investigation of change in dispersive behaviour during adhesive curing in multi-layered structures - Zeipert, Henning; von Germeten, Christian; Friesen, Olga; Claes, Leander; Johannesmann, Sarah; Henning, Bernd (Fortschritte der Akustik - DAGA 2023)

Bestimmung der Volumenviskosität mittels akustischer Absorptionsmessung - Claes, Leander (Fortschritte der Akustik - DAGA 2023)